Human immunodeficiency virus type 1 attachment to HeLa CD4 cells is CD4 independent and gp120 dependent and requires cell surface heparans. - Mondor, I; Ugolini, S; Sattentau, Q (1998)
The binding of human immunodeficiency virus type 1 (HIV-1) (Hx10) virions to two different cell lines was analyzed by using a novel assay based on the detection, by anti-HLA-DR-specific antibodies, of HLA-DR+ virus binding to HLA-DR- cells. Virion attachment to the CD4+-T-cell line A3.01 was highly CD4 dependent in that it was potently inhibited by CD4 monoclonal antibodies (MAbs), and little virus binding to the CD4- sister A2.01 line was observed. By contrast, virion binding to HeLa cells expressing moderate or high levels of CD4 was equivalent to, or lower than, binding to wild-type CD4- HeLa cells. Moreover, several CD4 MAbs did not reduce, but enhanced, HIV-1 attachment to HeLa-CD4 cells. CD4 was required for infection of HeLa cells, however, demonstrating a postattachment role for this receptor. MAbs specific for the V2 and V3 loops and the CD4i epitope of gp120 strongly inhibited virion binding to HeLa-CD4 cells, whereas MAbs specific for the CD4bs and the 2G12 epitopes enhanced attachment. Despite this, all gp120- and gp41-specific MAbs tested neutralized infectivity on HeLa-CD4 cells. HIV-1 attachment to HeLa cells was only partially inhibited by MAbs specific for adhesion molecules present on the virus or target cells but was completely blocked by polyanions such as heparin, dextran sulfate, and pentosan sulfate. Treatment of HeLa-CD4 cells with heparinases completely eliminated HIV attachment and infection, strongly implicating cell surface heparans in the attachment process. CD4 dependence for HIV-1 attachment to target cells is thus highly cell line specific and may be replaced by other ligand-receptor interactions.